1996
DOI: 10.1042/bj3130305
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase induced by epidermal growth factor negatively regulates the growth signal in primary cultured hepatocytes

Abstract: Transglutaminase (TGase) activity increased 2.5-fold at 6 h after treatment of rat hepatocytes with 17 nM epidermal growth factor (EGF). In the same manner, putrescine incorporation into the proteins of cells occurred in EGF-treated cells, but not in those pretreated with monodansylcadaverine (MDC), a TGase inhibitor, even in the presence of EGF. These results suggest that EGF-induced TGase was active and catalysed some cross-linkage reaction. Cycloheximide completely blocked the increase in TGase activity ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 24 publications
(39 reference statements)
1
38
0
Order By: Relevance
“…Given that the regulation of TGase expression is linked to PI3K activation and that growth factors frequently activate PI3K, we considered whether cotreatment of NIH3T3 cells with growth factors and RA would potentiate the induction of TGase expression, as well as the level of transamidation or GTP binding activity, compared with RA treatment alone. Epidermal growth factor (EGF) was chosen as the co-stimulus because it is not only an effective activator of PI3K but it also up-regulates TGase activity in hepatocytes (24). However, we found that rather than enhancing the induction rate or the expression levels of TGase, EGF suppressed the ability of RA to stimulate TGase expression.…”
mentioning
confidence: 60%
“…Given that the regulation of TGase expression is linked to PI3K activation and that growth factors frequently activate PI3K, we considered whether cotreatment of NIH3T3 cells with growth factors and RA would potentiate the induction of TGase expression, as well as the level of transamidation or GTP binding activity, compared with RA treatment alone. Epidermal growth factor (EGF) was chosen as the co-stimulus because it is not only an effective activator of PI3K but it also up-regulates TGase activity in hepatocytes (24). However, we found that rather than enhancing the induction rate or the expression levels of TGase, EGF suppressed the ability of RA to stimulate TGase expression.…”
mentioning
confidence: 60%
“…For example, tTG has been shown to stabilize the dimer of midkine, a growth/differentiation factor, and to enhance its activity (44). In primary hepatocytes, tTG can negatively regulate the growth signal stimulated by epidermal growth factor (46). To our knowledge, this is the first report that describes the post-translational modification of a viral structural protein by tTG.…”
Section: Discussionmentioning
confidence: 86%
“…TG2 has been reported to be a negative regulator to cell growth, for example, the induction of a shift from the proliferative to non-proliferative state by an increase in TG2-catalyzed isopeptide bonds in cells (2) or by induction of TG2-induced apoptosis (8,17). We have reported that inhibition of de novo synthesis of TG2 resulted in an increased growth of normal rat hepatocytes in the presence of epidermal growth factor (EGF) (15) or hepatocyte growth factor (HGF) (16). Taking these studies into consideration, it is possible that TG2 may be at least partially involved in suppression of hepatocyte growth during liver regeneration.…”
mentioning
confidence: 99%
“…Aliquots of the resultant supernatant were used as the cytosol fraction for the TG2 assay. TG2 activity of the cytosolic fraction was assayed by incorporation of [1, 4-14 C] putrescine into N, N'-dimethylcasein as described previously (15). The reaction mixture contained 50 mM Tris-HCl (pH 7.4), 10 mM dithiothreitol, 5 mM CaCl 2 , 0.5 mg of N, N'-dimethylcasein, and 1 mM putrescine including 1.85 kBq of radioactive putrescine.…”
mentioning
confidence: 99%